Quality assessment and improvement of post graduate family medicine training in the USA. Issue 5 (2nd September 2016) - Hoekzema, Grant S.; Maxwell, Lisa; Gravel, Joseph W.; Mills, Walter W.; Geiger, William; Honeycutt, J. David
Abstract: Background: In 2013, the World Organisation of Family Doctors published training standards for post-graduate medical education (GME) in Family Medicine/General Practice (FP/GP). GME quality has not been well-defined, other than meeting accreditation standards. In 2009, the Association of Family Medicine Residency Directors (AFMRD) developed a tool that would aid in raising the quality of family medicine residency training in the USA. Objective: We describe the development of this quality improvement tool, which we called the residency performance index (RPI), and its first three years of use by US family medicine residency (FMR) programmes. The RPI uses metrics specific to family medicine training in the USA to help programmes identify strengths and areas for improvement in their educational activities. Our review of three years of experience with the RPI revealed difficulties with collecting data, and lack of information on graduates' scope of practice. It also showed the potential usefulness of the tool as a programme improvement mechanism. Conclusions: The RPI is a nationwide, standardised, programme quality improvement tool for family medicine residency programmes in the USA, which was successfully launched as part of AFMRD's strategic plan. Although some initial challenges need to be addressed, it has the promise to aid family medicine residencies in their internal improvement efforts. This model could be adapted in other post-graduate training settings in FM/GP around the world.